1 over 3 subtracted from 2 over 3 would yield 1 over 3.
3/4
1 subtracted by 3 and one half = -2
2
1/12 - 2/3 = -7/12note:2/3 * 4/4 = 8/12thus 1/12 - 2/3= 1/12 - 8/12= -7/12
1 over 3 subtracted from 2 over 3 would yield 1 over 3.
3/4
4/6 - 3/6 = 1/6
2 subtracted by 3 = -1
2 over 9
It equals 3 over 6 which equals 1 over 2. Your welcome.
17 1/10
1 subtracted by 3 and one half = -2
2
7 1/3
1 1/4 - 3/4 = (1×4+1)/4 - 3/4 = 5/4 - 3/4 = (5-3)/4 = 2/4 = (1×2)/(2×2) = 1/2
1/12 - 2/3 = -7/12note:2/3 * 4/4 = 8/12thus 1/12 - 2/3= 1/12 - 8/12= -7/12